Direct oral anticoagulants in pediatric venous thromboembolism: Review of approved products rivaroxaban and dabigatran - Al-Ghafry, Maha; Sharathkumar, Anjali (Frontiers in Pediatrics, 2022)
Venous thromboembolism is a major hospital acquired complication in the pediatric population over the last two-decades, with a 130% increase from 2008 to 2019. Direct oral anticoagulants (DOACs) are a newer class of anticoagulant medication for the treatment and prophylaxis of VTEs that provide the primary advantages of an oral route of administration without a requirement to adjust dosing to achieve a therapeutic level. It is anticipated that these medications will quickly replace parental anticoagulants and clinicians should familiarize themselves with DOACs. In this article, we provide an overview of the pharmacological properties of DOACs, with a specific focus on two Food and Drug Administration approved DOACs for use in pediatric patients: rivaroxaban and dabigatran. Each drug’s characteristics are discussed along with data from their respective clinical trials.